Pengaruh Sector Industri, Tingkat Pendidikan, dan Investasi Asing terhadap Penyerapan Tenaga Kerja Sektor Industri di Indonesia - Agung Febrian Nurman; Sri Ulfa Sentosa (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This research aims to examined the effect of industry of wage, education and forign investment on the agricultural sector labor industry in Indonesia with the selected model is the Randon Effect Model (REM). The data used is panel data during the period 2014-2018, with thw twchnique of collecting documentation data and library studies obtained fromm relevant institution and agencies.The variables use are industry of wage (X1), education (X2), foreign invesment (X3), . the research method used is Ordinary Least Square (OLS). The estimation result show that industry of wage has a positive and its significant effect on the agricultural sector labor industry in Indonesia. Education has a negative and significant effect on the agricultural sector labor industry in Indonesia. foreign investment has a positife and its siknificant effect the agricultural sector industry Indonesia. Meanwhile simultaneously industry of wage, education and foreign investment effect the agricultural sector labor industry in Indonesia.